Phosphaturic mesenchymal tumor - Cheereth, Robin George; Augustine, Rogers P.; Nazar, Highness Tholakkara (International Surgery Journal, 2019)
Phosphaturic mesenchymal tumors (PMTs) are very unusual tumors, commonly associated with tumor induced osteomalacia (TIO). The tumor cells produce a peptide hormone-like substance known as fibroblast growth factor 23 (FGF23), which regulates phosphate levels. When FGF23 is over expressed by the tumor cells it leads to phosphaturia, which inturn causes mobilization of calcium and phosphate from bones, and decreased osteoblastic activity, which finally leads to severe osteomalacia. Usual presentation of PMT will be gradual muscular weakness and diffuse bone pain from pathologic fractures. The majority of PMTs are benign, malignant PMTs are extremely rare, but exist. However, very rarely PMT present without phosphaturia and TIO i.e., the nonphosphaturic variant. The challenge in diagnosis of PMT is due to the vague nature of the symptoms and lack of clinical suspicion. The diagnosis is often missed due to the rarity of PMTs. The usual location for PMT involves the extremities followed by head and neck sites. We report a case of a 37 year old male who presented to the outpatient department with a swelling in the left parotid region. He had no associated symptoms. CT scan showed a well-defined heterogeneous mass measuring 2.3 × 2.0 cm with calcification and soft tissue density seen superficially in the left pre auricular region. Per operatively the tumor was found to be intramuscular, embedded in the left masseter muscle. The final histopathology report was confirmative of phosphaturic mesenchymal tumor.